Integration of microfluidic chips with biosensors - Sekhwama, Masindi; Mpofu, Kelvin; Sudesh, Sivarasu; Mthunzi-Kufa, Patience (Discover applied sciences, 2024)
The potential threat posed by disease outbreaks to diagnostic instruments demands the development of more effective biosensor technologies to counteract the risks. Diseases like SARS-CoV-2, Ebola, malaria, cholera, and many more have demonstrated beyond the limits of health care that new advancements are required for early detection and diagnosis. The rising number of diseases outbreaks has led to an increasing demand for biosensors that are more effective and quicker to utilize in healthcare settings. A biosensor incorporated with microfluidic chips offers an improved detection compared to traditional or classical biosensors. Microfluidic chips improve the performance of the biosensors by allowing automation, mixing, separation, throughput processing, and transport of the analytes to desired reactors. A biosensor incorporated with a microfluidic chip has improved sensitivity, easy operation and can use small volumes of samples to process the results. The effectiveness of biosensors depends also on the materials used in its fabrication and there are many materials used for fabrication which are reviewed in this work. This paper reviews the potential advantages of the use of microfluidic chips to enhance the performance of biosensors, materials used to fabricate the chips, and potential electrodes incorporated into microfluidic chips which improve the detection time by shortening the processing time for biosensors at the point of care service. This work also reviews new technologies which are not previously addressed other reviews including, integration of cell-imprinted polymers with microfluidic sensors and delved into future technologies outlook. Article Highlights Highlight 1: This work reviews biosensors integrated with microfluidic chips. Highlight 2: The work reviews different materials used to fabricate microfluidic chips and their impact on biosensing. Highlight 3: The works also highlight the integration of electrodes into microfluidic chips to improve biosensor performance.